Dietary Tribulus Terrestris as a functional food combined with blood flow restriction to enhance the jump performance of basketball athletes: a randomized crossover study - Kong, J.; Li, J.; Xu, M.; Liu, T.; Xie, Z.; Li, T.; Liang, Y. (Frontiers in Nutrition, 2025)
Introduction: Tribulus terrestris (TT), a food-derived functional ingredient, may influence neuromuscular function via its bioactive compounds, but its acute effects on BFR-induced PAP and performance remain unknown. This study examined its short-term effects on neuromuscular performance after BFR-primed PAP in elite male basketball athletes (n = 20).